Evaluation of Corneal Curvature and Astigmatism in Patients with Persistent Pupillary Membrane by Partial Coherence Interferometry Measurements - Hu, Huiling; Yang, Mingmin; Du, Bing; Fang, Min; Liu, Xinhua; Wang, Jiantao (Ophthalmic research, 2020)
To evaluate and compare the corneal curvature and astigmatism in patients with persistent pupillary membrane (PPM) and healthy controls by partial coherence interferometry. This study included 14 eyes (9 patients) with PPM and 16 eyes (16 subjects) without PPM or other ocular disease, which were age and gender matched. The horizontal corneal radius of curvature (hCRC), vertical CRC (vCRC), average CRC (aveCRC), corneal astigmatic vectors (CAV), and axis were recorded using partial coherence interferometry. Uncorrected visual acuity and best corrected visual acuity (BCVA) were also recorded using a logMAR chart. In the PPM group, the vCRC (45.46 ± 0.52 D) was significantly larger than that in the control group (44.05 ± 0.24 D) (p = 0.009). The aveCRC in the PPM group (43.90 ± 0.46 D) was also significantly larger than that in the control group (43.34 ± 0.23 D) (p = 0.018). In the PPM group, the hCRC (42.35 ± 0.41 D) was significantly smaller than that in the control group (42.63 ± 0.24 D) (p = 0.049). The astigmatisms were with-the-rule in both groups. The absolute value of CAV in PPM group (3.17 ± 0.23 D) was significantly higher than that of control (1.36 ± 0.09 D) (p = 0.001). BCVA (0.42 ± 0.08) in PPM group was significantly worse than that in control (0.90 ± 0.03) (p = 0.009). The larger vertical and smaller horizontal corneal curvature resulted in higher corneal astigmatism with the rule, which is a characteristic feature in patients with PPM. More attention should be paid to astigmatism status and correction treatment for these patients.